Вплив флексоелекричного ефекту на гiстерезисну динамiку локального електромеханiчного вiдгуку напiвпровiдникiв з iонно-електронною провiднiстю - Morozovska, A. N.; Glinchuk, M. D.; Varenyk, O. V.; Udod, A.; Scherbakov, C. M.; Kalinin, S. V. (Publishing house "Academperiodika", 2018)
Strong coupling among electrochemical potentials, concentrations of electrons, ions, and strains mediated by the flexoelectric effect is a ubiquitous feature of moderate conductors, in particular, MIECs, the materials of choice in devices ranging from electroresistive and memristive elements to ion batteries and fuel cells. Corresponding mechanisms that govern bias-concentration-strain changes (Vegard expansion, deformation potential, and flexoelectric effect) are analyzed. Notably, that the contribution of the flexoelectric coupling to a local surface displacement of the moderate conductors is a complex dynamic effect which may lead to the drastic changing of the material mechanical response, depending on the values of flexoelectric coefficients and other external conditions. Numerical simulations have shown that the flexoelectric impact on the mechanical response ranges from the appearance of additional strain components, essential changes of a hysteresis loop shape and orientation, and the appearance of complex twisted hysteresis loops.